Savings and investment decisions in a poor oil economy: beyond the textbook case - Collier, P; Gunning, J (2007)
The current commodity boom is a major opportunity for poor countries exporting exhaustible resources such as oil. In the past oil booms were often mismanaged leaving the country with lower long run income. Many countries are now well aware that booms require intricate savings and investment strategies and some are use legislation to lock-in such strategies. However, the textbook characterization of optimal savings and investment is not appropriate for poor oil economies. Such countries have imperfect access to international capital markets and traded construction services and they run a risk that a future populist regime will run down the assets saved for future downturns. We investigate the effects of these characteristics on optimal savings and investment and use a simulation model to illustrate their importance.